2014
DOI: 10.5588/ijtld.14.0152
|View full text |Cite
|
Sign up to set email alerts
|

Primary lung cancer coexisting with active pulmonary tuberculosis

Abstract: The present study demonstrates that lung cancer combined with active pulmonary TB most frequently presents as squamous cell carcinoma, with a male predominance. The overall survival of lung cancer patients did not change even with concomitant active TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 0 publications
2
15
1
1
Order By: Relevance
“…In this study, LC stage was advanced (76.5%). Similar results were reported in previous studies (22,23,25,26).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, LC stage was advanced (76.5%). Similar results were reported in previous studies (22,23,25,26).…”
Section: Discussionsupporting
confidence: 93%
“…Squamous cell carcinoma was the most common histological subtype in our study (41.2%) that was similar to the studies of Morales-Cardia et al Varol Y et al (22,23). But, adenocarcinoma was the most common subtype in other series (20,24).…”
Section: Discussionsupporting
confidence: 91%
“…It is less than that reported by Varol et al where it was seen in 1.1%. 27 Bronchoscopy was the procedure of choice for central tumours and transthoracic FNAB for peripheral tumours in our study. Overall the best diagnostic procedure was transthoracic FNAB (61.2% of all diagnosis).…”
Section: Resultsmentioning
confidence: 77%
“…Conversely, Liang et al found that only adenocarcinoma was significantly associated with TB [6]. Nevertheless, very recent study revealed that the predominant type was still SCC [17]. Though it depends on the regional distribution of lung cancer histology it is rather SCC which is more frequent in TB patients.…”
Section: Discussionmentioning
confidence: 96%